Application of the Halal Concept in the Era Industrial Revolution 4.0 in Indonesia - Reza, Fachrul; Tinggogoy, Filo Leonardo (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
This study aims to determine the application of the halal concept in the era of the industrial revolution 4.0 in Indonesia. The basis of this research was carried out because Indonesia was ranked 2nd as the country with the highest number of Muslim tourists based on data released by the OIC in 2019. The research method used is descriptive, which tries to answer the existing problems based on the data. The theory used refers to the marketing concept with Islamic teachings proposed by Bin Ya'qub al-Tahir and Sharif Murad, namely product, price, place and promotion. The results of the study show that the halal industry has a fairly good development potential, but it is unfortunate that the Muslim community still lacks awareness of the benefits and importance of consuming halal food, through the marketing strategy of halal food in the industrial era 4.0. The industrial revolution 4.0 presents great challenges and opportunities for the advancement of the halal industry in Indonesia and the world. Thus, the readiness of sharia economic stakeholders is needed in solving the complex problems of digitalization. Sharia economic actors are required to continue to innovate in product and market research, and it is a mandate to advance the halal industry as a superior product in boosting the popularity of the sharia economy